The effects of salary and fringe benefits to the job satisfaction of law librarians in Metro Manila - Capitin, Dorothy B. (1994)
This study sought to find out the effect of salaries and fringe benefits to the job satisfaction of law librarians in Metro Manila. Also, it discussed the prevailing salaries, fringe benefits, factors affecting the salaries and fringe benefits, and the job satisfaction level of the law librarians.